Synthesis, Physical, Chemical and DFT Properties of Cobalt(II), Nickel(II), Copper(II), and Zinc(II) Complexes with Polydentate Schiff Base Derived from 1,2,4-Triazole - Zuhair, Fatima Haitham; Al-Garawi, Zahraa Salim; Al-jibouri, Mahmoud Najim; Mohamed, Gehad Genidy; Abdallah, Abanoub Mosaad (Indonesian Journal of Chemistry, 2024)
The work describes the synthesis and spectral investigation of cobalt(II), nickel(II), copper(II), and zinc(II) complexes with (E)-4-((4-nitrobenzylidene)amino)-5-(3,4,5-trimethoxyphenyl)-4H-1,2,4-triazole-3-thiol (L). The new ligand was synthesized through three steps, first the preparation of 3,4,5-trimethoxyphenylhydrazide salt, the ring closure of potassium hydrazide salt with excess of hydrazine hydrate followed by condensation of the derivative 4-amino-5-(3,4,5-trimethoxyphenyl)-4H-1,2,4-triazole-3-thiol with 4-nitrobenzaldehyde in glacial acetic acid. The physical and spectroscopic properties of the ligand and its complexes were well investigated and theoretically studied. The experimental results were compatible with their expected compositions. Based on the spectral data, metal complexes with coordination numbers 6 and 4 were proposed, with L functioning as a bidentate ligand. The metal complexes displayed an octahedral geometry around bivalent cobalt, nickel, and zinc tetrahedral environment. Density functional theory calculations (DFT) were conducted to investigate the geometry optimization of the synthesized ligand L and its Co(II) complex and to confirm the structure of the ligand by comparing its experimental vibrational and NMR spectra with the corresponding DFT calculated spectra. The DFT results revealed the participation of nitrogen and sulfur atoms of imine and thione groups in coordination with the metal ions beside the good agreement with the experimental data of elemental analyses and spectroscopic measurements.